Performance Enhancement via Real-Time Image-Based Beam Tracking for WA-OWC With Dynamic Waves and Mobile Receivers - Di, Yujie; Xu, Anzi; Chen, Lian-Kuan (Journal of lightwave technology, 2024)
Intensified underwater activities have driven the escalating demand for reliable, flexible, and high data-rate underwater communication links. Optical wireless communication (OWC) emerges as the most promising technology for short- to medium-range communication, facilitating the real-time high-speed transmission of information from undersea to an aerial vehicle which can subsequently relay the information to a terrestrial station. However, establishing a robust water-air link confronts two primary challenges: (i) beam wandering due to the time-varying refraction when the light beam passes through the undulating ocean surface and (ii) the drone's movement when it hovers above the ocean surface. This paper experimentally demonstrated a real-time imaged-based beam tracking system to mitigate beam misalignment due to dynamic waves and receiver movement over a 0.14-m underwater and 1.83-m free-space OWC channel. Experimental results evince a notable reduction in the standard deviation of the received light spot offset from the receiver. Moreover, the tracking system can proficiently accommodate receiver velocities of up to 150 cm/s while maintaining a paltry packet loss rate (PLR) below 10%. By addressing the combined effects of dynamic waves and moving receivers, the proposed beam tracking system successfully enables a 70% reduction in PLR and an order of magnitude decrease in bit error rate (BER). This results in a substantial 17-fold surge in maximum throughput, from 50 Mbit/s to 850 Mbit/s. The experimental results validate the feasibility and effectiveness of the beam tracking system for vanquishing the detrimental effects in the complex water-air OWC (WA-OWC) channel and supporting high-speed data transmission.